PUVA Induced Bullous Pemphigoid in a Patient with Mycosis Fungoides - Birgül Özkesici; Saliha Koç; Ayşe Akman-Karakaş; Ertan Yılmaz; İbrahim Cumhur Başsorgun; Soner Uzun (Case Reports in Dermatological Medicine)
Background. Bullous pemphigoid is an autoimmune subepidermal blistering skin disease in which autoantibodies are directed against components of the basement membrane. The disease primarily affects the elderly people and in most of the patients inducing factors cannot be identified. Herein, we report a case of BP that occurred in a patient who was receiving PUVA therapy for the treatment of mycosis fungoides. Main Observation. A 26-year-old woman with mycosis fungoides developed blisters while receiving PUVA therapy. On physical examination tense bullae on the normal skin, remnants of blisters, and erosions were observed on her breasts, the chest wall, and the upper abdomen. Histopathological investigations revealed subepidermal blisters with eosinophilic infiltration and in direct immunofluorescence examination linear deposition of IgG along the basement membrane zone was observed. The diagnosis of bullous pemphigoid was also confirmed by ELISA and BIOCHIP mosaic-based indirect immunofluorescence test. Conclusions. PUVA therapy is an extremely rare physical factor capable of inducing bullous pemphigoid. So the development of blistering lesions during PUVA therapy may be suggestive sign of a bullous disease such as bullous pemphigoid and it should be excluded with proper clinical and laboratory approaches immediately after withdrawal of PUVA therapy.